2014
DOI: 10.1111/mono.12133
|View full text |Cite
|
Sign up to set email alerts
|

Vii. The History of Physical Activity and Academic Performance Research: Informing the Future

Abstract: The study of physical activity, physical fitness, and academic performance research are reviewed from a historical perspective, by providing an overview of existing publications focused on children and adolescents. Using rigorous inclusion criteria, the studies were quantified and qualified using both meta-analytic and descriptive evaluations analyses, first by time-period and then as an overall summary, particularly focusing on secular trends and future directions. This review is timely because the body of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
71
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 118 publications
(145 reference statements)
7
71
0
1
Order By: Relevance
“…Unlike adults, who lead idiosyncratic lives, virtually all children in western culture receive some form of formal education, which provides the opportunity to assess how PA (or other health behaviors) influences performance on scholastic assessments, including standardized academic achievement tests. Although there is a general lack of consensus, the vast majority of findings point to a beneficial relation of PA and aerobic fitness to scholastic performance, with higher marks observed for academic achievement tests and classroom-based assessments [15][16][17]. …”
mentioning
confidence: 97%
“…Unlike adults, who lead idiosyncratic lives, virtually all children in western culture receive some form of formal education, which provides the opportunity to assess how PA (or other health behaviors) influences performance on scholastic assessments, including standardized academic achievement tests. Although there is a general lack of consensus, the vast majority of findings point to a beneficial relation of PA and aerobic fitness to scholastic performance, with higher marks observed for academic achievement tests and classroom-based assessments [15][16][17]. …”
mentioning
confidence: 97%
“…67 Physical activity is increasingly being recognized as an important determinant of 68 cognitive and neural functioning in middle childhood 7 and adulthood, 8,9 in addition to its various A c c e p t e d M a n u s c r i p t 6 other physiological and psychosocial benefits. [9][10][11] Findings from systematic and meta-analytical 70 reviews indicate that higher amounts of physical activity improve cognitive functioning and 71 academic achievement in school-aged children and youth 7,12,13 and reduce the risk of age-related 72 cognitive decline, dementia, and Alzheimer's disease in adulthood. 9,14-17 However, little is 73 known about the relationship between durations, intensities, frequencies, or patterns of physical 74 activity and cognitive development in early childhood among apparently healthy children (i.e., 75 no diagnosed disease).…”
mentioning
confidence: 99%
“…2,3 Research has shown that school-based PA interventions are effective for improving health outcomes and also for improving educationally relevant behavioral outcomes such as time on task [4][5][6] and academic achievement. 7,8 To experience optimal health benefits, it is recommended that children aged 6-17 years accrue at least 60 minutes of moderate to vigorous PA (MVPA) per day. 9 Several studies have provided evidence that elementary-school-aged children need at least 12,000 steps daily to reach this target.…”
mentioning
confidence: 99%